2011
DOI: 10.1007/s00709-011-0296-z
|View full text |Cite
|
Sign up to set email alerts
|

Variations on a theme: plant autophagy in comparison to yeast and mammals

Abstract: Autophagy is an evolutionary conserved process of bulk degradation and nutrient sequestration that occurs in all eukaryotic cells. Yet, in recent years, autophagy has also been shown to play a role in the specific degradation of individual proteins or protein aggregates as well as of damaged organelles. The process was initially discovered in yeast and has also been very well studied in mammals and, to a lesser extent, in plants. In this review, we summarize what is known regarding the various functions of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 110 publications
0
81
0
1
Order By: Relevance
“…Core components of autophagy in yeast, mammals, and plants can be generally divided into three functional groups: (1) ATG9 recycling system including ATG1, ATG2, ATG9, ATG13, ATG18, and ATG27; (2) ATG6/Beclin1 and PI3K/ VPS34 nucleation complex including ATG6, ATG14, VPS15, and VPS34; (3) the two ubiquitin-like conjugation systems, ATG8 and ATG12, which are made up of ATG3, ATG4, ATG5, ATG7, ATG8, ATG10, ATG12, and ATG16 (Xie and Klionsky, 2007;Avin-Wittenberg et al, 2011). The identification and function of some core proteins in plants are briefly discussed below in the order of their involvements in the autophagy process: initiation, vesicle nucleation, expansion, and autophagosome formation (Fig.…”
Section: Morphology Of Autophagy and The Relative Componentsmentioning
confidence: 99%
“…Core components of autophagy in yeast, mammals, and plants can be generally divided into three functional groups: (1) ATG9 recycling system including ATG1, ATG2, ATG9, ATG13, ATG18, and ATG27; (2) ATG6/Beclin1 and PI3K/ VPS34 nucleation complex including ATG6, ATG14, VPS15, and VPS34; (3) the two ubiquitin-like conjugation systems, ATG8 and ATG12, which are made up of ATG3, ATG4, ATG5, ATG7, ATG8, ATG10, ATG12, and ATG16 (Xie and Klionsky, 2007;Avin-Wittenberg et al, 2011). The identification and function of some core proteins in plants are briefly discussed below in the order of their involvements in the autophagy process: initiation, vesicle nucleation, expansion, and autophagosome formation (Fig.…”
Section: Morphology Of Autophagy and The Relative Componentsmentioning
confidence: 99%
“…Among these, the machinery required for autophagosome formation is constituted by several core complexes: the ATG1/Unc-51-like kinase complex, the phosphoinositide 3-kinase (PI3K) complex, the Atg9 reservoir and its trafficking machinery, and two ubiquitin-like conjugation systems, including Atg12 and Atg8 (Xie and Klionsky, 2007; Despite tremendous progress made in our understanding of the molecular mechanisms underlying autophagic pathways in yeast and mammals, autophagy studies in plants are still in their infancy. Although most of the ATG genes required for autophagy have been identified in plants ( Avin-Wittenberg et al, 2012;Liu and Bassham, 2012), the molecular mechanism whereby ATG proteins regulate autophagosome formation in plant cells remains to be examined. Models for plant autophagosome formation are primarily deduced from those in yeast or mammals and are poorly characterized Li and Vierstra, 2012;Liu and Bassham, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The ATG8 protein has been widely used to monitor autophagy in many systems (9) because, unlike other ATG proteins, this protein firmly binds to the autophagosome membrane through a covalent bond to phosphatidylethanolamine (PE). Most of the core ATG proteins are conserved in land plants (10)(11)(12) and in evolutionarily distant algae, including freshwater species, such as the model green alga Chlamydomonas reinhardtii (herein referred to as Chlamydomonas) (13) and marine species (14). Our current knowledge about autophagy in algae is still limited compared to our knowledge about autophagy in other eukaryotes, but recent studies, mainly performed in Chlamydomonas, have shown that this degradative process is elicited under various stress conditions.…”
mentioning
confidence: 99%